Application of Molecular Diagnostics to the Evaluation of the Surgical Approach to Thyroid Cancer - Miccoli, Paolo (Current Genomics, 2014)
Recent important studies that include long-term follow-up have shown that BRAF and RAS mutations can have negative implications for disease recurrence and survival. BRAF positivity has been shown to be associated with decreased survival and is an independent predictor of poor prognosis. Reliable pre-operative identification of high-risk papillary thyroid cancer (PTC) patients may productively guide initial surgical management since reoperative neck surgery is associated with increased morbidity. However, it is probably too early to conclude that at present it is possible to tailor surgical therapy patient by patient only on the basis of their mutational status. Other important parameters, not including molecular testing, represented by some specific morphological aspects, still play an important role, probably still more significant than molecular diagnostics, such as neck ultrasonography. Pre-operative knowledge of BRAF-positive PTC could alter the initial surgical treatment for at least 20% of patients and can potentially prevent the increased morbidity associated with reoperative neck exploration. However, additional multi-institutional and randomized studies will be needed to further define the role of the pre-operative identification of BRAF positivity to guide not only the initial extent of total thyroidectomy (TT) but also the need for and extent of lymphadenectomy.
Keywords: Hemithyroidectomy